Sub‐Thermionic Negative Capacitance Field Effect Transistors with Solution Combustion‐Derived Hf0.5Zr0.5O2 (Adv. Funct. Mater. 43/2021). (20th October 2021) - Pujar, Pavan; Cho, Haewon; Gandla, Srinivas; Naqi, Muhammad; Hong, Seongin; Kim, Sunkook
Abstract : Negative Capacitance In article number 2103748, Sunkook Kim and co‐workers effectively utilize combustion chemistry in solution‐processed ferroelectric‐Hf0.5 Zr0.5 O2 to realize negative capacitance and effectively utilize the same to achieve ultra‐low‐power operation of MoS2 transistors via sub‐60 mV/dec switching. This is the first study extending the applicability of solution‐processed oxide ferroelectrics to a completely new avenue of high mobility, ultra‐low‐power electronics.